2013
DOI: 10.1038/modpathol.2012.164
|View full text |Cite
|
Sign up to set email alerts
|

CD4 helper T cells, CD8 cytotoxic T cells, and FOXP3+ regulatory T cells with respect to lethal prostate cancer

Abstract: Prostate cancer represents a major contributor to cancer mortality, but the majority of men with prostate cancer will die of other causes. Thus, a challenge is identifying potentially lethal disease at diagnosis. Conflicting results have been reported when investigating the relationship between infiltration of lymphocytes and survival in prostate cancer. One of the mechanisms suggested is the recruitment of regulatory T cells (T regs ), a subpopulation of T cells that have a role in promoting tumor growth. T r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
2
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 36 publications
6
81
2
4
Order By: Relevance
“…They did not, however, investigate how the different subsets of T lymphocytes contributed to the clinical outcome. Ness et al showed that the negative prognostic effect may be mediated primarily through CD8 + lymphocytes rather than the overall density of T lymphocytes as measured by CD3 positivity [283], while Davidsson et al attributed the poor prognostic effect to T regs in the prostate cancer microenvironment [284]. Others have reported a correlation between FOXP3 + TILs in prostate cancer and biochemical recurrence [285], though Vesalainen et al reported that tumors with dense TILs were associated with higher survival rates than tumors with absent or decreased TILs [286].…”
Section: Tils In Genitourinary Carcinomasmentioning
confidence: 99%
“…They did not, however, investigate how the different subsets of T lymphocytes contributed to the clinical outcome. Ness et al showed that the negative prognostic effect may be mediated primarily through CD8 + lymphocytes rather than the overall density of T lymphocytes as measured by CD3 positivity [283], while Davidsson et al attributed the poor prognostic effect to T regs in the prostate cancer microenvironment [284]. Others have reported a correlation between FOXP3 + TILs in prostate cancer and biochemical recurrence [285], though Vesalainen et al reported that tumors with dense TILs were associated with higher survival rates than tumors with absent or decreased TILs [286].…”
Section: Tils In Genitourinary Carcinomasmentioning
confidence: 99%
“…Although conflicting results have been highlighted when investigating the relationship between infiltration of lymphocytes and survival in prostate cancer, Davidsson et al [73] performed a case-control study nested in a cohort of men treated with transurethral resection of the prostate and diagnosed incidentally with prostate cancer. Although infiltration of both CD4 ?…”
Section: The Adaptive Immunitymentioning
confidence: 99%
“…17 One study compared the infiltration of both T helper and T cytotoxic cells between men who died of prostate cancer and those who survived for 10 years with prostate cancer. 18 Their results suggested that patients with increased numbers of CD4 þ Tregs in their prostate tumor environment had an increased risk of dying from prostate cancer. Since the approval of the dendritic-based cancer vaccine sipuleucel-T (Provenge) by the FDA in 2010, 19 an increasing number of immunotherapeutic agents are being tested in clinical trials for CRPC.…”
Section: Discussionmentioning
confidence: 98%
“…18 Their results suggested that patients with increased numbers of CD4 þ Tregs in their prostate tumor environment had an increased risk of dying from prostate cancer. Since the approval of the dendritic-based cancer vaccine sipuleucel-T (Provenge) by the FDA in 2010, 19 an increasing number of immunotherapeutic agents are being tested in clinical trials for CRPC. The aim of cancer immunotherapy is to overcome the weak immunogenicity of tumorassociated antigenic material and to provoke a robust immune response to cancer cells.…”
Section: Discussionmentioning
confidence: 98%